The Relationship Between Body Image and Self-Confidence Among Post-Mastectomy Breast Cancer Patients at Grandmed Hospital Lubuk Pakam - Arfah May Syara; Farhah Zaqwa Khairunnisa Damanik; Simson Sinuhaji; Muhammad Reza Fahlevi Hanafi; Yuni Suharnida Lubis (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Carcinoma mammae is a malignant condition of breast tissue characterized by the uncontrolled proliferation of abnormal cells that form tumors, which may metastasize to other organs and become life-threatening if not properly treated. Cancer cells generally originate from the milk-producing lobules or the breast ducts. Mastectomy, as a primary therapeutic intervention, often leads to significant physical changes that can affect patients’ body image and self-confidence. This study aimed to analyze the relationship between body image and self-confidence among post-mastectomy carcinoma mammae patients. This research employed a quantitative approach with a survey design using questionnaires. The sample consisted of 51 respondents selected through a total sampling technique at Grandmed Hospital Lubuk Pakam. The frequency distribution results indicated that the majority of respondents had a positive body image perception, with 48 individuals (94.1%) agreeing and 3 individuals (5.9%) disagreeing. Meanwhile, the level of self-confidence among respondents was also relatively high, with 44 individuals (86.3%) agreeing and 7 individuals (13.7%) disagreeing. Statistical analysis using the chi-square test revealed a significant relationship between body image and self-confidence (p-value = 0.84; α < 0.05), indicating that the alternative hypothesis was accepted. These findings highlight the importance of effective body image management in enhancing patients’ self-confidence. Therefore, psychological interventions such as counseling, psychoeducation, and peer support are essential to facilitate patients’ adaptation and self-acceptance following mastectomy.